The Influence Of Task Load, Student Engagement, And New Student Selection On Learning Achievement Of Students At SMP Negeri 63 Batam - Prasetyo, Windra; Realize, Realize (Jurnal Ekonomi, 2024)
This research aims to identify the influence of task load, student engagement, and new student selection on the learning achievement of students at SMP Negeri 63 Batam. The research method used is quantitative with a survey approach. The population of this study includes of all 220 seventh grade students at SMP Negeri 63 Batam. Data were collected through questionnairesand analyzed using multiple linear regression. The result of the study indicated that task load, student engagement, and new student selection have a positive and significant effect on students learning achievement with an F value of 130.513 > F table value of 2.646 and a significance level of < 0.001. This research is expected to contribute to the improvement of strategies and the quality of education more effectively at SMP Negeri 63 Batam.